SPEECH ACTS IN PSYCHOLINGUISTICS CLASS SETTING IN POSTGRADUATE PROGRAM - Lalu Suhirman (IJOTL-TL: Indonesian Journal of Language Teaching and Linguistics, 2016)
This article aims to identify forms of speech act in the lecture  of  psychololinguistics class setting and to elaborate  types of speech act approaches in the lecture. The subjects of this research are an English instructor and 11 psycholinguistic participants of  Post Graduate Program of UNM. Data  taken from this study were the utterances  produced by instructor/lecturer and the participants  during the class discussion. Instruments of this study were observation format, field notes, tape recorder/and handy-camp, and the script of utterances. The result of analysis indicated that there were three types of speech acts: locutionary actillocutionary act, and perlocutionary act. The speech acts has an effect on the feelings, thoughts or actions of either the speaker or the listener. The speech acts change readers or listeners mindset.